Young researchers/artists/teachers: protagonists from the university - Carvalho, Ananda (Farol, 2024)
This paper consists of a report about the Jovens pesquisadores/artistas/professores Conference held at the XV Seminário Capixaba sobre o Ensino da Arte. The panel gives voice to the power of students with the participation of finalists and graduates of the Degree in Visual Arts course at Ufes: Jaíne Muniz, Matheusa Moreira, Geisa da Silva and Henrique Tavares. The four speakers brought reports of experiences, highlighting the intertwining of their experience at Ufes and practices in the art circuit, in schools and in non-school education. All trajectories are based on the construction of protagonisms under a decolonial bias (in Grada Kilomba's understanding), articulated as a response to the glaring inequality of representation of minorities within the field of art.
Keywords: Decolonial art; Contemporary art; Youth; Teaching Art; University